NIVO KVANTITATIVNIH PROMJENA SPECIFIČNO-MOTORIČKIH SPOSOBNOSTI NOGOMETAŠA POD UTICAJEM SITUACIONOG TRENINGA - Izet Bajramović; Munir Talović; Haris Alić; Eldin Jelešković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Target of this research was to analyse levels of transformation of situational motoric abilities and their level of developement in 12 - 14 years young soccer players. Research analysis was made on results of initial and fi nal status of sample of 11 variables which mesured situational motoric abilities. Global quantitative transformation developement levels were estimated by discriminative analysis. The concept of training program allways had a goal to solve a problem from the game which occured in past played games in competition. Duration of training program was six months, planed with 72 training units and 8 games in organized soccer league competition for 12 - 14 years young soccer players. Discriminative analysis resulted with signiticant quantitative impovement in variables which determined power shoots at the ball, coordination and techniqual manipulation with the ball, and shooting leg precision abilities.